Detection and Antibiotic Sensitivity Pattern of Gardnerella vaginalis Isolated from Bacterial Vaginosis Patients Attending Chittagong Medical College Hospital - Ara, Nura Nasrin Rowshan; Husain, Md Anwar; Akter, Nasima; Ahmed, Shakeel; Rahman, Md Mostafizur; Nigar, Mafruha; Akhter, Shamima (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background: Now a day’s bacterial vaginosis is an extremely common health problem for women in the world which causes many complications both in the pregnancy and non-pregnancy states. G. vaginalis is most important cause of bacterial vaginosis. Methods: A prospective observational study was conducted to detect G. vaginalis in bacterial vaginosis and their sensitivity patterns on patients attending at the outpatient Department of Gynaecology and Obstetrics of Chittagong Medical College Hospital, Chittagong. A total of 170 sexually active female in the age group of 15-45 years, with abnormal vaginal discharge were selected for the study. A detailed history and a thorough clinical examination of all the cases were done. Results:In this study 38(22.35%) Gardnerella vaginalis were isolated by culture and bacterial vaginosis was detected by different methods 47(27.65%). Antimicrobial resistance is one of the major public health threats. So antimicrobial sensitivity pattern of the organisms should be done at regular intervals. Conclusion: In this study Gardnerella vaginalis showed high (52.63%) resistant to most commonly used metronidazole and 100% sensitive to clindamycin. Chatt Maa Shi Hosp Med Coll J; Vol.16 (1); Jan 2017; Page 48-53